Restoring assembly and activity of cystathionine β-synthase mutants by ligands and chemical chaperones - Kopecká, Jana; Krijt, Jakub; Raková, Kateřina; Kožich, Viktor (Journal of inherited metabolic disease, 2011)
Misfolding and aggregation of mutant enzymes have been proposed to play role in the pathogenesis of homocystinuria due to cystathionine β-synthase (CBS) deficiency. Chemical chaperones have been recently shown to facilitate proper assembly of several CBS mutants. To asses the number of patients that may respond to chaperone therapy, we examined the effect of selected CBS ligands and osmolytes on assembly and activity of 27 CBS mutants that represent 70% of known CBS alleles. The mutant enzymes were expressed in a bacterial system, and their properties were assessed by native Western blotting and sensitive liquid chromatography tandem mass spectrometry (LC-MS/MS) assay, respectively. We studied the chaperoning activity of δ-aminolevulinic acid (δ-ALA)-a heme precursor-and of three osmolytes betaine, 2-aminoethanesulfonic acid (taurine), and glycerol. Fourteen mutants responded by at least 30% increase in the amount of correctly assembled tetramers and enzymatic activity to the coexpressional presence of either 0.5 mM δ-ALA, 100 mM betaine, and/or 750 mM glycerol. Eight of these mutants (p.R266K, p.P49L, p.R125Q, p.K102N, p.R369C, p.V180A, p.P78R, p.S466L) were rescuable by all of these three substances. Four mutants showed increased formation of tetramers that was not accompanied by changes in activity. Topology of mutations appeared to determine the chaperone responsiveness, as 11 of 14 solvent-exposed mutations were substantially more responsive than three of 13 buried mutations. This study identified chaperone-responsive mutants that represent 56 of 713 known patient-derived CBS alleles and may serve as a basis for exploring pharmacological approaches aimed at correcting misfolding in homocystinuria.
Keywords: alely; Ligands; Aminolevulinic Acid; Glycerol; Homocystinuria; Protein Multimerization; Polymorphism, Single Nucleotide; Humans; glycerol; ligandy; kyselina aminolevulová; molekulární chaperony; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; konformace proteinů; Protein Binding; homocystinurie; cystathionin-beta-synthasa; jednonukleotidový polymorfismus; Cystathionine beta-Synthase; Mutant Proteins; Protein Conformation; mutantní proteiny; Alleles; Escherichia coli; lidé; Betaine; Taurine; Molecular Chaperones; Protein Folding; sbalování proteinů; betain; vazba proteinů; taurin; multimerizace proteinu